Computer models to simulate ion flow in neurons - Clay, Robert Christopher (2017)
In this thesis the Drift Diffusion enhanced Hodgkin Huxley model is developed. This model uses the Drift Diffusion equations to model the bulk solutions both within a neuron and in the surrounding extracellular media. The Hodgkin Huxley ion channel behaviour is incorporated into the membrane regions through the use of an altered diffusion coefficient. Firstly the model is applied to the case of intracellular and extracellular media separated by a single membrane. Secondly the model is applied to a cell within a restricted extracellular space. This takes a slice through a cell and is therefore termed a double membrane model, since there are two membrane layers. Finally the model is used to determine whether there is any charge and field buildup on a gold surface located 100 nm from the cell. The results from this could then be used in future to model Surface Plasmon Resonance experiments which may form the basis of novel neuronal activity detectors.